Thinking historically : educating students for the twenty-first century - Lévesque, Stéphane 1971- (University of Toronto, 2009)
Two simple but profound questions have preoccupied scholars since the establishment of history education over a century ago: what is historical thinking, and how do educators go about teaching it? In Thinking Historically, Stéphane Lévesque examines these questions, focusing on what it means to think critically about the past. As students engage with a new century already characterized by global instability, uncertainty, and rivalry over claims about the past, present, and future, this study revisits enduring questions and aims to offer new and relevant answers.\Drawing on a rich collection of personal, national, and international studies in history education, Lévesque offers a coherent and innovative way of looking at how historical expertise in the domain intersects with the pedagogy of history education. Thinking Historically provides teacher educators, and all those working in the field of history education, ways of rethinking their practice by presenting some of the benchmarks, in terms of procedural concepts, of what students ought to learn and do to become more critical historical actors and citizens.\As questions regarding history education impinge upon educators with greater force than ever, this timely study explores different ways of approaching and engaging with the discipline in the twenty-first century.